Swedish newspapers 1871-1906 - Språkbanken Text (University of Gothenburg, 2024)
Svenska tidningar 1871–1906 contains a selection of digitized versions of Swedish newspapers from 1871 to 1906. It is part of the so called Kubhist corpus which was digitized at Kungliga biblioteket (KB). One newspaper was randomly selected from each year. For each newspaper two pages were selected, the second and fourth. All pages were automatically processed using advanced document layout analysis where each segment in the digitized page was framed and numbered. Each segment was processed with Abbyy FineReader version 11 and was manually transcribed by a transcription company who specializes in double-keying.

This particular subset contains 74 pages, 45,445 segments and 337,635 words in total.

It was produced as a part of the project Evaluation and refinement of an enhanced OCR-process for mass digitisation financed by RJ (dnr IN18-0940:1) for the period of 2019-2020.

Svenska tidningar 1871–1906 innehåller ett urval av digitaliserade versioner av svenska tidningar från 1871 till 1906. Det är en del av den så kallad Kubhist corpus which was digitized at Kubhist-korpus som digitaliserades av Kungliga biblioteket (KB). En tidning valdes slumpmässigt from varje år. För varje tidning valdes två sidor, andra och fjärde. Sidorna bearbetades automatiskt med hjälp av avancerad dokumentlayoutanalys där varje segment i den digitaliserade sidan inramades och numrerades. Vidare har varje segment bearbetades med Abbyy FineReader version 11 och slutligen transkriberades manuellt av ett transkriptionsföretag som är specialiserat på så kallad double-keying.

Denna datamängd innehåller 74 sidor, 45,445 segment och 337,635 ord totalt.

Materialet producerades inom projektet Utvärdering och förfining av en förbättrad OCR-process för massdigitalisering som finansieras av RJ (dnr IN18-0940: 1) för perioden 2019-2020.
Svenska tidningar 1871-1906
Keywords: Language Technology (Computational Linguistics); fraktur; historical newspapers; OCR; reference text; corpus; Natural Language Processing; Språkbehandling och datorlingvistik